Pendampingan Pembelajaran Seni Rupa Berkarya Seni Grafis Cetak Tinggi di SMPN 1 Mlati, Sleman, Yogyakarta - Rony Siswo Setiaji; Zulfi Hendri; Kharisma Creativani; Alifia Zahra Khoirunisa; Denny Wahyu Triawan (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2024)
Fine arts learning really participates in growing and developing all the competencies possessed by students. Fine arts learning at school includes creative activities to gain knowledge and skills in producing creative works of art, including relief printmaking. The fine arts learning service program for creating relief printmaking at SMP N 1 Mlati, Sleman, Yogyakarta provides benefits for the development of cultural arts materials in schools, because creating relief printmaking on canvas bag media is a new thing for students. The activities of this program include pre-program implementation activities, which are activities for preparing materials, lesson plans, media, and learning models. Program implementation activities are visual arts learning activities creating relief printmaking for class IX. Post-implementation activities of the program are evaluation activities of the community service program, namely filling out items by students related to the implementation of the community service program. Overall the results of the evaluation of the program that we implemented received a positive response as much as 87.3% of students strongly agreed that the program was in accordance with their needs. 88.26% strongly agreed that the program could increase learning motivation and a score of 88.03% stated that the program could encourage students' abilities. Then in the program aspect it can be useful for students obtaining a score of 89.9% and in the program aspect giving rise to student empowerment obtaining a score of 85.6%.